PENGARUH PERKEMBANGAN KEUANGAN TERHADAP EMISI CO2 DI INDONESIA - Muhammad Madyan; Deni Kusumawardani; Hasbi Ash Shidiq (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
This study aims to examine the effect of financial developments on CO2 emissions in Indonesia from 1980 to 2019 by adding financial developments as a moderating variable using multiple linear regression analysis. This study extended the STIRPAT framework as a research model. The results of the study found that financial developments had a negative effect on CO2 emissions and significantly weakened the positive effects of economic growth on CO2 emissions. In addition, economic growth, energy consumption, and urbanization negatively affect environmental quality. The results revealed that financial developments have an important role in improving environmental quality and controlling CO2 emissions.